PENGARUH PENGGUNAAN MEDIA YOUTUBE TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN SEJARAH DI SMA NEGERI 2 BAYUNG LENCIR - Wulandari, Anggi; Ahyani, Nur; Sri Nindiati, Dina (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2025)
This study aims to find out whether there is an influence of the use of youtube media on student learning outcomes in history subjects at SMA Negeri 2 Bayung Lencir. The method used is Experiment with the Quasi Experiment type. The sample selection used the Purposive Sampling technique consisting of class X.1 as a control class of 25 students and class X.3 as an experimental class of 25 students. Data collection techniques were obtained from observation, tests and documentation. Meanwhile, the data analysis technique consisted of normality test, homogeneity test and hypothesis test. So based on the results of the hypothesis test, the result of tcount = 4.891 and ttable value = 1.677 with α=0.05 and df=48 then 4.891 ≥ 1.677 so that the tcount ≥ ttable then Hα is accepted and Ho is rejected. So it can be concluded that in this study there is an influence of the use of youtube media on student learning outcomes in history subjects at SMA Negeri 2 Bayung Lencir.